A modular isolated battery‐integrated multiport step‐up DC–DC converter for hybrid energy applications. Issue 16 (19th June 2022) - Mahmoodieh, Mir Esmaeel Seyed; Babaei, Ebrahim; Sabahi, Mehran
Abstract: In this paper, a modular isolated battery‐integrated multiport step‐up dc–dc converter is designed for simultaneous energy transfer from multiple renewable energy sources (RESs) to a load. The proposed converter offers a plug‐and‐play capability of input sources where each input can be connected to and disconnected from the converter. The power generation shortage/surplus can be managed by a battery inserted into a bidirectional port. Also, charging/discharging durations of battery are independent of switching duty ratios for input sources. In the presented converter, inputs are connected in parallel with a common ground through individual step‐up dc–dc cells while outputs are connected in series with voltage doubler rectifiers (VDRs) to achieve higher voltage gains and lower voltage stress on output capacitors. Moreover, the leakage inductances of the isolated transformers with dc blocking capacitors provide quasi‐resonant operation to alleviate high turn‐off currents of switches and hard‐switching in VDR diodes. Due to interactions of converter control loops, a MIMO closed‐loop control system is designed to regulate the output voltage and output power of input sources at references. The simulation and experimental results obtained for three inputs verify performance of the developed converter in different modes.